2005
DOI: 10.1128/aem.71.10.6159-6164.2005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns ofCryptosporidiumOocyst Shedding by Eastern Grey Kangaroos Inhabiting an Australian Watershed

Abstract: The occurrence of Cryptosporidium oocysts in feces from a population of wild eastern grey kangaroos inhabiting a protected watershed in Sydney, Australia, was investigated. Over a 2-year period, Cryptosporidium oocysts were detected in 239 of the 3,557 (6.7%) eastern grey kangaroo fecal samples tested by using a combined immunomagnetic separation and flow cytometric technique. The prevalence of Cryptosporidium in this host population was estimated to range from 0.32% to 28.5%, with peaks occurring during the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
1
38
1
Order By: Relevance
“…In contrast, C. macropodum was identified in captive western grey and red kangaroos during summer (Thompson, 2007). The pathogenicity of C. macropodum to marsupials is relatively unknown, but data indicate that this species is adapted to marsupials as oocyst shedding in eastern grey kangaroos ranged from 10 to 2.0 ϫ 10 6 oocysts per gram and that samples with high oocyst loads were not associated with diarrhea (Power et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In contrast, C. macropodum was identified in captive western grey and red kangaroos during summer (Thompson, 2007). The pathogenicity of C. macropodum to marsupials is relatively unknown, but data indicate that this species is adapted to marsupials as oocyst shedding in eastern grey kangaroos ranged from 10 to 2.0 ϫ 10 6 oocysts per gram and that samples with high oocyst loads were not associated with diarrhea (Power et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In another recent study, C. macropodum was identified in 6 of 10 fecal samples from western grey kangaroos and 3 of 30 samples from red kangaroos (Thompson, 2007). The eastern grey kangaroo study demonstrated cyclic shedding patterns, with C. macropodum dominating during the cooler months and C. fayeri dominating during periods when the population contained high numbers of juveniles (Power et al, 2005). In contrast, C. macropodum was identified in captive western grey and red kangaroos during summer (Thompson, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations